Design Improvement of Pindad Mini Excavator Boom using Finite Element Method - Zairullah Azhar; Azhari Sastranegara (Journal of Mechanical Engineering and Mechatronics, 2020)
This paper presents the analysis of mini excavator excava 50 with a focus on the boom component. The boom component is a component that has a heavy workload. The material used in the existing design is SM490A. The results of the analysis are still not safe because allowable stress is less than working stress. The material in the existing design was replaced with Hardox 400. The design is declared safe. However, the costs of the product have increased because Hardox 400 materials are more expensive than SM490A. To reduce the costs of the product, design improvement is needed to optimize the use of material. The design improvement method that uses in this study is according the optimization method, that is sizing and shape optimization. After improvement the design, to predict how long the boom component can be used, fatigue life prediction is calculated using Goodman’s theory